Latin American Folklore: Roots, Genres, Uniqueness - A. F. Kofman (Ибероамериканские тетради)
Latin American folklore is a heterogeneous phenomenon, encompassing different levels, which has been determined by the historical conditions of its formation, existence and evolution. The so-called folklore criollo, which dates back to the Spanish folk poetry brought by the Spaniards to America during the colonial period, is an important part of the Latin American folklore. The specific character of historical and socio-economic circumstances that influenced the formation of the folklore criollo, explain its relatively late formation, as well as the transformation and reinterpretation of the original Spanish popular poetic tradition. As a result of syncretisation, Creole folklore has incorporated various elements of the folk art of the indigenous peoples, including those of African origin. The main genres of Creole folklore are romance, décima (glossa) and copla, which have evolved since their birth in Spain and later in the New World, where they came with waves of Spanish immigrants. The specific conditions of life in the American colonies, in which such psychological qualities as courage, bravery, aggressive ness and violence became the norm of existence, determined the content, motifs and plot of folklore. At the same time, romantic poetry was «folklorised», it was adapted to the collective environment, its themes were simplified. Folk songs and romances were given a sentimental, artificially dramatic character of exaggerated suffering. Romantic songs have achieved great popularity, as they exist today in different Latin American countries in different forms or genres, namely the corrido, the song ranchera, the yaraví, the mulisa, among others. The example of the folklorisation of the romantic style was the tango song that was formed in Argentina and Uruguay as a massive amateur composition in the 1920s. Different genres of Creole folklore are present with their own specificity in all Latin American and Caribbean countries and deserve new studies taking into account new conditions of social and human development.